If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(2x + 6) = 90 Reorder the terms: 9(6 + 2x) = 90 (6 * 9 + 2x * 9) = 90 (54 + 18x) = 90 Solving 54 + 18x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + 18x = 90 + -54 Combine like terms: 54 + -54 = 0 0 + 18x = 90 + -54 18x = 90 + -54 Combine like terms: 90 + -54 = 36 18x = 36 Divide each side by '18'. x = 2 Simplifying x = 2
| 5-9[5-(9y-4)]= | | (sqrt(4y+1))-(sqrt(y-2))=3 | | 7b-5=6b-2 | | 6x-3=2x+23 | | 16n+8=-36n | | 3(v-2)=-3v+36 | | 10-3*a=4 | | 40-5x=110-25x | | fg-9h=j | | 16n+8=-36 | | 0.75=p-180 | | 7b-2=5b+2 | | 6*a+4=11 | | 0.25(p-180)=p | | z^8-6=9 | | -91+5x=-3x+141 | | -8(x-6)=3+3(1-5x) | | 3x^2-6x+8=3 | | 0.75=p+180 | | 8x^3-4x^2-40x=0 | | -6x-49=51-11x | | 5x-2(3x-2)=2 | | 8x=-9x+-1 | | x(3)= | | ax+fx=s | | y=-2x+g | | 9n+(7n+28)=50 | | 10(x+11)=-30 | | 23x-7-14x+4=20x-3-11x+12 | | (2ab+7a+1)=(8ab+9) | | 4+9-4*3+8*7-25*2= | | P-(-19)=23 |